Comparative analysis of services from soft open points using cost–benefit analysis. (1st March 2023) - Deakin, Matthew; Sarantakos, Ilias; Greenwood, David; Bialek, Janusz; Taylor, Phil C.; Walker, Sara
Abstract: Soft Open Points (SOPs) are power electronic-based devices which can replace Normally Open Points (NOPs) in distribution networks. They can improve network performance by enabling controllable power transfer between adjacent feeders. This flexible meshing can provide a wide range of services, including loss reduction, reduced renewables curtailment, improved reliability, reinforcement deferral, or enabling flexibility services. This paper proposes a novel framework, based on the Cost–Benefit Analysis methodology, to quantify and compare the cost-effectiveness of SOPs for providing each of these five value streams. The framework includes the development of mathematical models that encapsulate the key variables that drive competitive SOP use cases, as well as providing detailed analysis to determine quantitative estimates for each of the parameters. Results suggest that, whilst all services could be cost-effective, that reinforcement deferral and reduced DG curtailment are most likely to find wide usage. It is also suggested that the fast response time of SOPs as compared to conventional NOPs is unlikely to be a viable value proposition for improving reliability via conventional loss of load metrics such as energy not supplied. A detailed case study demonstrates that in marginal cases, where a SOP has a similar system net benefit compared to Business-as-Usual, that all services need to be considered rather than just single value streams in isolation. It is concluded from the research that there are multiple potential competitive applications for SOPs in future distribution networks. Highlights: A novel comparative framework for considering Soft Open Points (SOPs) is proposed. Benefits of five services are modelled, and techno-economic parameters identified. A range of credible estimates for all of these critical parameters are evaluated. Reinforcement deferral and DG curtailment reduction appear most promising services. Interactions between services become very important when SOP benefits are moderate.